A Study on the Mechanism of Herb-Partitioned Moxibustion at the Navel Based on the Gut-Brain Axis Theory in the Prevention and Treatment of Insomnia via the BDNF/TrkB Pathway - Ye, Xiaona; Sun, Chao; Liu, Qingyin; Zhao, Yingying; Lin, Xiuqun; Zhao, Xinglin; Han, Xingjun (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: To examine the impact of navel moxibustion, a form of herb-partitioned moxibustion applied at the belly button, on Brain-Derived Neurotrophic Factor (BDNF), Tyrosine Kinase receptor B (TrkB) and 5-Hydroxytryptamine (5-HT) levels in rats with PCPA-induced insomnia. Additionally, to investigate the mechanism by which navel moxibustion improves insomnia. Materials and Methods: 27 Specific Pathogen Free (SPF)-grade male three-month- old SD rats were randomly divided by weight into the normal group, model group and navel moxibustion group. Except for the normal group, the latter two groups were administered Para-Chlorophenylalanine (PCPA) via gastric intubation to establish the insomnia rat model. After successful modeling, the navel moxibustion group received treatment, while the normal and model groups received a sham treatment consisting of binding with non-woven fabric at the Shenque (CV 8) point, with treatments administered once every three days for a total of five treatments. After the completion of the treatment, the animals were humanely euthanized in order to obtain hippocampal tissue. The collected samples were then subjected to HE staining, real-time quantitative PCR and Western blot analysis for a comparative assessment of hypothalamic BDNF, TrkB and 5-HT gene and protein expression levels before and after the application of isolated moxibustion therapy. Results: HE staining revealed significant pathological symptoms in the hypothalamic tissue of the model group, while the navel moxibustion group showed darker nuclear staining, increased density and more orderly arrangement, resembling the normal group. Compared to the normal group, the model group exhibited reduced gene expression of BDNF, TrkB and 5-HT in the hypothalamic tissue (p<0.05), with lower protein levels of BDNF (p<0.05), TrkB (p<0.05) and 5-HT. After navel moxibustion treatment, the levels of BDNF, TrkB and 5-HT genes were significantly elevated compared to the model group (p<0.05), as were the protein expression levels of BDNF (p<0.05), TrkB and 5-HT. Conclusion: The navel moxibustion method can improve cellular damage in the hypothalamic tissue of PCPA-induced insomnia rats, elevating the gene and protein levels of BDNF, TrkB and 5-HT, thereby confirming the role of navel moxibustion in neurotransmission and effectively alleviating insomnia.
Keywords: 5-hydroxytryptamine (5-HT); Brain-Derived Neurotrophic Factor (BDNF); Insomnia; Tyrosine Kinase receptor B (TrkB)